Too Sensitive or Just Self-Aware?: A Narrative Analysis of Filipino Generation Z with Emotional Vulnerability in the Workplace - Saila L Bareng; Jurelyn Lustria; Quenee Palomeras; Jason Manaois (Psikoislamika, 2025)
The study explores Filipino Generation Z’s emotional vulnerability in the workplace. The study focuses on their experiences, thoughts, and feelings about being emotionally vulnerable, sensitive, and self-aware in the workplace. In sharing their stories, five participants born between 2000–2006 were able to explain their personal, positional, and ideological understanding of emotional vulnerability in the workplace. Generation Z employees’ narratives cover three chapters: beginning - first experience of emotional vulnerability in the workplace; middle: dealing with emotional vulnerability in the workplace; and end reflection on emotional vulnerability in the workplace. The study identified the nine (9) themes that defined the participant’s collated experiences: (1) experience of emotional distress from conflict and lack of support in the workplace; (2) experience of enduring emotional distress with professionalism and patience; (3) experience of coping with emotional distress and finding emotional balance; (4) perceived role as a learner navigating workplace dynamics; (5) perceived role as disregarded voice and vulnerable professional; (6) perceived role as advocates for employee support and well-being; (7) the value of emotional awareness and adaptability; (8) the value of professionalism; and (9) the value of sensitivity. Generation Z employees collectively advocate the importance of creating emotional intelligence, self-awareness, and sensitivity-promoting environments in the workplace.